2007
DOI: 10.1080/00016350701477581
|View full text |Cite
|
Sign up to set email alerts
|

The erosion-inhibiting effect of TiF4, SnF2, and NaF solutions on pellicle-covered enamelin vitro

Abstract: TiF(4) gave the best protection against acid attack. SnF(2) provided significant protection only after 2 min of acid exposure, while NaF had no significant protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 30 publications
4
45
1
13
Order By: Relevance
“…Furthermore, fluoride was often added into the remineralization solution at higher concentrations than those found in human saliva (0.022 ppm) 49 because its profound effect on the enamel remineralization is well-established in the field. 34,61,62 It could be possible that the application of the more efficient remineralizing agents such as higher concentrations of fluoride and metal compounds (Sn 2þ , Ti 2þ ) 63 would result in the detection of erosion inhibition by reflection analysis.…”
Section: Analysis Of the Erosion Progression Among Enamel Specimens Rmentioning
confidence: 99%
“…Furthermore, fluoride was often added into the remineralization solution at higher concentrations than those found in human saliva (0.022 ppm) 49 because its profound effect on the enamel remineralization is well-established in the field. 34,61,62 It could be possible that the application of the more efficient remineralizing agents such as higher concentrations of fluoride and metal compounds (Sn 2þ , Ti 2þ ) 63 would result in the detection of erosion inhibition by reflection analysis.…”
Section: Analysis Of the Erosion Progression Among Enamel Specimens Rmentioning
confidence: 99%
“…Thereby, SnF 2 containing toothpastes and solutions showed a better protective capability against erosion-like lesions than NaF agents. 10,11,23,24 Ganss et al 5 found that erosive mineral loss was nearly completely inhibited by AmF/SnF 2 and SnF 2 solutions, while NaF solutions were less effective and AmF and AmF/NaF showed no significant effect (all solutions: 250 ppm F -). The results of this study suggest that not only the fluoride, but also the respective cation could influence the protective efficacy of the fluoride compound.…”
Section: Introductionmentioning
confidence: 99%
“…However, in most of these studies, the fluoride compounds were applied with different concentration of F, 24 different pH 10,11,23 or in different formulations (toothpaste, solution, gel or varnish), 19 which makes the interpretation of the results regarding to the impact of the respective cations difficult. Moreover, in some in vitro experiments, the fluoride agents were not applied on pellicle-covered samples but on polished surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of TiF 4 to reduce carious demineralisation suggested that it might be also an effective agent in preventing erosive dental loss. In several recent in vitro 3,[11][12][13] and few in situ studies 14,15 it was shown that TiF 4 reduced dental erosion significantly and was more effective than sodium, amine or stannous fluoride.…”
Section: Introductionmentioning
confidence: 99%